Environmental assessment sourcebook (World Bank Washington, D.C.US, 1991)
Provides practical guidance for designing sustainable World Bank assisted projects. Supplies information on bank policies and procedures, guidelines, precedents and 'best practice' regarding the environment. Focuses on those operations with major potential for negative environmental impact, such as new infrastructure, dams and highways. Briefly examines projects with relatively less negative potential such as maintenance and rehabilitation.
DC